Peran Analisis Mengenai Dampak Lingkungan Dan Hukum Lingkungan Dalam Kerusakan Pengelolaan Lingkungan Hidup Di Indonesia - Muhammad Yusuf Muda Azka; Irwan Triadi (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Analysis of environmental impacts and environmental law are one unit so that humans, when carrying out development, do not damage the territory or environment where creatures live side by side. The aim of this research is to determine the role of environmental impact analysis and environmental law in environmental management in Indonesia. The method used in this writing, namely the normative juridical method, is research aimed at finding and formulating legal arguments through analysis of the subject matter by conducting research based on literature and analyzing primary legal materials and secondary materials which is carried out by studying statutory regulations and literature. others in the form of books, journals, research results related to problems, namely the Role of Environmental Impact Analysis and Environmental Law in Damaging Environmental Management in Indonesia. Preventive environmental law enforcement aims to prevent environmental damage and/or pollution. Regulations regarding environmental protection and enforcement are contained in Law Number 32 of 2009.